2009
DOI: 10.1088/0022-3727/42/9/095005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of crystal orientation on magnetic properties of hcp Co nanowire arrays

Abstract: In this paper we develop a convenient way to control the direction of uniaxial magnetocrystalline easy axis in ac electrodeposited hcp Co nanowire arrays. The c-axis of hcp cobalt can be oriented parallel or perpendicular to the long axis of the wire by adjusting the temperature of the electrolyte. Magnetic characterizations suggest that the direction of the hcp c-axis plays an important role in the magnetization reversal process. A three-dimensional object oriented micromagnetic framework code was used to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 22 publications
0
33
1
1
Order By: Relevance
“…[1][2][3][4] Lately, magnetic nanowires (Co, Fe, and Ni) have been studied experimentally and by simulations. [5][6][7][8] For example, depending on their diameters, the magnetization of these nanowires is known to reverse via either transverse walls or vortex walls. In thin ferromagnetic nanowires (diameter < 40 nm), a simple domain wall nucleates and propagates along the nanowire axis, while the reversal of thick nanowires (diameter more than 40 nm) is achieved via localized curling or vortex mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Lately, magnetic nanowires (Co, Fe, and Ni) have been studied experimentally and by simulations. [5][6][7][8] For example, depending on their diameters, the magnetization of these nanowires is known to reverse via either transverse walls or vortex walls. In thin ferromagnetic nanowires (diameter < 40 nm), a simple domain wall nucleates and propagates along the nanowire axis, while the reversal of thick nanowires (diameter more than 40 nm) is achieved via localized curling or vortex mode.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that the magnetostatic coupling between nanostructures will strongly influence their response to an external field, and therefore also influence subsequent device performance. [8][9][10] However, it is difficult to observe the magnetization of individual nanowires and even more difficult to observe the crystalline grains within a nanowire. Some bulk measurements, such as first order reversal curves (FORC), can be used to observe averages and distributions of magnetizations and coercivities.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various methods developed to prepare nanowires, electrodeposition combined with anodic aluminium oxide(AAO) template method is applied widely due to its convenience, inexpensiveness and large-scale processing [4,12,16]. It has been demonstrated that the magnetic properties of Co nanowires can be effectively modulated through varying the diameter [18,21,22]. However, the diameter variation of nanowires results in a change in the storage density or a rise in the interaction between neighboring nanowires, which will severely affect the performance of the potential devices [2].…”
Section: Introductionmentioning
confidence: 99%
“…A uniaxial magnetocrystalline anisotropy of 4100 J/m 3 with random direction was present in each cell. This anisotropy value was 10% of the fcc-Co anisotropy, K fcc-Co , based on the assumption that the anisotropy of the thin film is less than that of bulk, 27 and the weak crystalline texture leads to an approximately random anisotropy. 28 K fcc-Co is about 10% of the hcp-Co anisotropy, K hcp-Co = 4.1 × 10 5 J/m 3 .…”
Section: Methodsmentioning
confidence: 99%